MASUK BARANG PADA PERUSAHAAN PT. INDOFARMA GLOBAL MEDIKA MEDAN - Zefri Andika; Agustina Pratiwi; Indra Fauzi (Jurnal Inovasi Penelitian, 2022)
The purpose of this study was to determine whether the practice of the information system used was in accordance with the procedures established by the company, and to determine the Faktors that could affect the lead time of the goods out process. The research method used is descriptive analysis method, which is a method that aims to describe the company based on the actual facts that occurred in the company. The data needed in this study include standard operating procedures (SOP), flow charts, applications related to accounting information systems, especially in the process of handing over goods at PT. Indofarma Global Medika Medan Branch. Based on the results of research and discussion, it can be concluded that the entry and exit of goods at PT. Indfarma Global Medika Medan Branch has met the standards set by the company. Internal Faktors that affect the process of out of lead time items such as lack of communication between warehousemen, requests for goods that do not match through the warehouse admin, and errors in updating circulating data. Meanwhile, external Faktors affect the length of time the process takes to get the tally sheet, examiners and forklift operators.